INCIDENCE OF HYPOGLYCEMIA FOLLOWING "INSULIN CHASE": A SINGLE-CENTER CLINICAL AUDIT - Loh, Jia Ling; Nordin, Hidayatil Alimi Bin Keya; Tong, Chin Voon; Mohamednor, L (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Hyperkalemia poses a significant threat due to its potential to induce fatal cardiac arrhythmias. "Insulin chase," or a combination of intravenous insulin, calcium gluconate, and dextrose, is given to rapidly lower serum potassium levels. Potential risks of this regime include hypoglycemia. This study aims to determine the incidence of hypoglycemia following the administration of "insulin chase" in our center, explore associated risk factors, and assess adherence to blood glucose (BG) monitoring when this regime is administered. METHODOLOGY This was a retrospective observational study. Medical records of all adult patients who received insulin chase treatment at Hospital Putrajaya between January 1, 2023, and December 31, 2024, were retrieved and reviewed. RESULT A total of 187 patients received insulin chase during the study period. The mean age was 58 years (SD 15.9). The majority were male patients (63.1%), and more than half (58.8%) had background diabetes mellitus. The incidence of hypoglycemia post-insulin chase was 16.6%. Patients who developed hypoglycemia had a significantly higher median creatinine level (678 umol/l vs. 349 umol/l, p = 0.005). Prior use of sulfonylurea was also significantly associated with an increased risk of hypoglycemia (26.3% vs. 8.8%, p = 0.031). Factors such as age, gender, race, presence of diabetes mellitus, and prior insulin use were not found to be significantly associated with the development of hypoglycemia. Almost one-quarter of patients (23.5%) did not have BG checked prior, and only 40.6% had BG monitoring planned post-insulin chase. CONCLUSION This audit demonstrated a 16.6% incidence of hypoglycemia post-insulin chase. Renal impairment and prior sulfonylurea use were significant risk factors. There is a need to improve the planning and implementation of pre- and post-treatment glucose monitoring to prevent hypoglycemia.